Direct vs. Anonymous Feedback: Teacher Behavior in Higher Education, with Focus on Technology Advances. (3rd July 2015) - Corelli, Angelo
Abstract: The paper aims at analyzing how feedback and valuations from students impact on the behavior of the teacher. It offers a broad view on the effectiveness of feedback, based on the direct experience of the author, and the discussions and interviews held in the previous years with other faculties. What follows is an in depth analysis of the students reaction to various learning approaches and how their opinion and feedback are formed. The behavior of teachers is then described, according to the actual feedback received by the students, especially relating to how the form of feedback influences the will of the instructor to accept and implement it. A description of the role of technology is taken into account then, with in depth analysis of the impact of such a methodology on the general behavior of the teacher. The conclusion is that higher education is characterized by high sensitivity on both sides. Students can reveal strong and even harsh opinions, which are usually followed by well determined reactions by the teacher in terms of the adjustments made to the course structure and teaching material.